2008
DOI: 10.1111/j.1440-1746.2007.05096.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of diclofenac in reducing post‐endoscopic retrograde cholangiopancreatography pancreatitis

Abstract: Wang ZH, Mo JZ, Xiao SD. Effects of thalidomide in experimental models of post-endoscopic retrograde cholangiopancreatography pancreatitis. J. Gastroenterol. Hepatol. 2007; 22: 371-6. 18 He ZJ, Winston JH, Yusuf Te et al. Intraductal administration of an NK1 receptor antagonist attenuates the inflammatory response to retrograde infusion of radiological contrast in rats: implications for the pathogenesis and prevention of ERCP-induced pancreatitis. Pancreas 2003; 27: e13-7. 19 Khoshbaten M, Khorram H, Madad L, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 44 publications
6
105
0
1
Order By: Relevance
“…This difference was statistically significant, with P < 0.01. No patients in this clinical trial developed necrotizing pancreatitis or required surgical intervention [18,44] . We showed that, in the diclofenac group, pancreatitis was seen less than in the control group, but this was not statistically significant.…”
Section: Table 3 Serum Amylase Level (Mean ± Se Iu/l) Following Ercpmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference was statistically significant, with P < 0.01. No patients in this clinical trial developed necrotizing pancreatitis or required surgical intervention [18,44] . We showed that, in the diclofenac group, pancreatitis was seen less than in the control group, but this was not statistically significant.…”
Section: Table 3 Serum Amylase Level (Mean ± Se Iu/l) Following Ercpmentioning
confidence: 99%
“…Also, the drug was not effective in the subgroup of patients with SOD, the very group at highest risk [9] . Khoshbaten et al [18] have reported a randomized controlled study that compared 100 mg rectal diclofenac with placebo in 100 patients who underwent high-risk ERCP. To select high-risk cases, only those undergoing pancreatography (with or without cholangiography) were enrolled.…”
Section: Table 3 Serum Amylase Level (Mean ± Se Iu/l) Following Ercpmentioning
confidence: 99%
See 1 more Smart Citation
“…There was, however, a significant protective effect among patients with inadvertent pancreatography (2% vs 19%). 132 Khoshbaten et al 133 reported that RNSAIDs significantly reduced PEP (26%-4%) in a study where pancreatography was the criterion for entry.…”
Section: Post-ercp Prophylaxismentioning
confidence: 99%
“…The results of RCTs using nitroglycerine, ceftazidime, somatostatin, octreotide, antiprotease drugs, glucocorticoids, drugs reducing sphincter of Oddi pressure, antioxidant drugs, heparin, and Interleukin-10 have been disappointing [4]. Some studies have shown a benefit with NSAIDs [10][11][12][13][14][15][16][17][18], but a practice survey study performed some years ago showed that they were not widely used [19]. The main reason quoted was insufficient supporting evidence, but the authors speculate that clinicians' scepticism related to the failure of many other large studies with other pharmacological agents also played an important role.…”
Section: Introductionmentioning
confidence: 99%